A comparative study on the measurement properties of Dermatology Life Quality Index (DLQI), DLQI‐Relevant and Skindex‐16. (24th November 2021) - Szabó, Á.; Brodszky, V.; Rencz, F.
Summary: Background: Dermatology Life Quality Index (DLQI) and Skindex‐16 are among the most commonly used dermatology‐specific health‐related quality‐of‐life (HRQoL) instruments. DLQI has two common scoring methods, the original and the DLQI‐Relevant (DLQI‐R) modification. Head‐to‐head comparisons of the measurement properties of the DLQI, DLQI‐R and Skindex‐16 are currently lacking. Objectives: We aim to compare the measurement properties of the DLQI, DLQI‐R and Skindex‐16. Methods: We analysed data from 618 patients with self‐reported physician‐diagnosed dermatological conditions from a cross‐sectional survey carried out in Hungary in early 2020. DLQI, DLQI‐R and Skindex‐16 were compared in terms of ceiling and floor effects, informativity, convergent validity and known‐group validity. Results: Mean DLQI, DLQI‐R and Skindex‐16 total scores were 3·76 ± 5·03, 4·11 ± 5·34 and 29·36 ± 26·62, respectively. Among patients with a DLQI/DLQI‐R total score of zero, 64% reported problems on Skindex‐16. Overall, 23–38% of patients with 'not relevant' responses on DLQI items 3 (shopping/home/gardening), 7 (working/studying), 8 (interpersonal problems) and 9 (sexual difficulties) reported problems on their corresponding Skindex‐16 items. Average relative informativity (Shannon's evenness index) was the highest for Skindex‐16 (0·85), followed by DLQI‐R (0·66) and DLQI (0·54). DLQI, DLQI‐R and Skindex‐16 demonstrated similar convergent validity. DLQI was able to better discriminate between known groups of patients based on overall skin‐related HRQoL impairment, whereas DLQI‐R and Skindex‐16 performed better with respect to self‐perceived health status. Conclusions: Skindex‐16 seems to be more sensitive than DLQI/DLQI‐R in capturing mild impairment in HRQoL. Our findings help to provide a fuller understanding of the difference between DLQI, DLQI‐R and Skindex‐16 and support the informed choice of instrument for clinical and research purposes. Abstract : What is already known about this topic? Dermatology Life Quality Index (DLQI) and Skindex‐16 are among the most commonly used dermatology‐specific instruments to measure health‐related quality of life (HRQoL). DLQI has an alternative scoring, DLQI‐Relevant (DLQI‐R), developed in 2018. So far, no studies have provided a comprehensive head‐to‐head comparison of the measurement properties of the DLQI, DLQI‐R and Skindex‐16. What does this study add? We systematically compared the measurement performance of DLQI, DLQI‐R and Skindex‐16 items and overall scales. Skindex‐16 showed lower floor effect, better informativity, and similar convergent and known‐group validity to the DLQI and DLQI‐R. Nearly two‐thirds of patients with a DLQI/DLQI‐R total score of zero reported problems on Skindex‐16. Many patients with 'not relevant' responses on DLQI items 3 (shopping/home/gardening), 7 (working/studying), 8 (interpersonal relations) and 9 (sexual difficulties) reported problems on their corresponding Skindex‐16 items. What are the clinical implications of this work? In patients with mild symptoms, DLQI and DLQI‐R might not be able to capture small impairments in HRQoL, and thus, the Skindex‐16 seems more suitable in this population. Our findings help to provide a fuller understanding of the difference between existing dermatology‐specific HRQoL measures and support the informed choice of instrument for clinical practice, research, treatment and financial guidelines. Linked Comment:  A. Evers. Br J Dermatol 2022; 186 :395–396 . Plain language summary available online